Effectiveness of the Use of Near-Infrared Spectroscopy to Treat Acute Type A Aortic Dissection Complicated with Limb Ischemia: Report of a Case - Tamura, Kentaro (Ann Vasc Dis, 2015)
We report an effectiveness of the use of near-infrared spectroscopy to evaluate the limb perfusion, which helps to continuously measure the tissue oxygen index of bilateral legs in treating acute type A aortic dissection complicated with limb ischemia. A 62-year-old man underwent total arch replacement for acute type A aortic dissection with limb ischemia. Intraoperative retrograde true lumen perfusion via bilateral femoral arteries during cardiopulmonary bypass improved ischemic condition of bilateral legs before the resection of primary intimal tear, and the use of near-infrared spectroscopy made it possible to assess additional revascularizations to the lower limbs were required or not.